2021
DOI: 10.3390/v13071407
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Evolution of Type 2 Vaccine-Derived Polioviruses in Individuals with Primary Immunodeficiency Diseases

Abstract: The oral poliovirus vaccine (OPV), which prevents person-to-person transmission of poliovirus by inducing robust intestinal immunity, has been a crucial tool for global polio eradication. However, polio outbreaks, mainly caused by type 2 circulating vaccine-derived poliovirus (cVDPV2), are increasing worldwide. Meanwhile, immunodeficiency-associated vaccine-derived poliovirus (iVDPV) is considered another risk factor during the final stage of global polio eradication. Patients with primary immunodeficiency dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…All these substitutions shared amino acid mutations in VP1‐143 (I→T). This site is a nonantigenic site surface residue and a known attenuation site, which is identified as the main attenuated determinant site of the Sabin 2 strain 34 . A type 2 VDPV in 2010 showed a VP1‐99 mutation (K→Q), which is a non‐synonymous mutation encoding antigenic site 1.…”
Section: Discussionmentioning
confidence: 99%
“…All these substitutions shared amino acid mutations in VP1‐143 (I→T). This site is a nonantigenic site surface residue and a known attenuation site, which is identified as the main attenuated determinant site of the Sabin 2 strain 34 . A type 2 VDPV in 2010 showed a VP1‐99 mutation (K→Q), which is a non‐synonymous mutation encoding antigenic site 1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recombination also occurs in the capsid‐coding region near the end of the VP1 coding region in certain PV strains 40,41 . In contrast, approximately all the reported recombination events involved in iVDPVs cases are only reportedly related to three OPV‐strain types 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…40,41 In contrast, approximately all the reported recombination events involved in iVDPVs cases are only reportedly related to three OPV-strain types. [42][43][44] In fact, in both cVDPVs and iVDPVs, mutation and recombination potentially elicit the reversion of key attenuated determinants and changes in temperature-sensitive phenotypes 45,46 ; the Ningxia iVDPV strains are no exception. Whole-genome analysis of these iVDPV isolates revealed that multiple nucleotide substitutions and deduced amino-acid substitutions were found to randomly distribute across the genome as compared to the respective Sabin strains; moreover; we found that they were all Sabin 3/Sabin 1 recombinants, sharing a common junction site near the 3ʹ -end of the 2C coding region.…”
Section: Discussionmentioning
confidence: 99%
“…However, cVDPV2 is most associated with cVDPV outbreaks. It is a widespread cVDPV and is responsible for most cases of AFP [ 89 ]. It has been shown that cVDPV strains are recombinant.…”
Section: Emergence Of Vaccine-derived Poliovirus Strainsmentioning
confidence: 99%